2004
DOI: 10.1111/j.1467-8683.2004.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

The Independence Paradox: (im)possibilities facing non‐executive directors in The Netherlands

Abstract: The paper adds to our knowledge of what non-executive directors do, knowledge which is still in its infancy. More specifically, it reports the findings of a survey among more than 250 Dutch non-executive directors regarding their roles and limitations. Although the majority agreed that monitoring is their main duty, they also expressed doubts whether they are really able to carry out this "watchdog role" effectively. The primary limitation is sought in the asymmetry of information which gives rise to the so-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 19 publications
9
52
0
1
Order By: Relevance
“…In the case of outside directors,the negative effect on both ROA and ROE even though statistically insignificant is consistent with Hooghiemstra and van Manen, (2004) but inconsistent with the agency theory's prescription which predicted positive effect on CFP with board composition of majority outside directors. As part of their findings Hooghiemstra and van Manen, (2004) suggested that stakeholders are generally not satisfied with the supervisory role of outside directors.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In the case of outside directors,the negative effect on both ROA and ROE even though statistically insignificant is consistent with Hooghiemstra and van Manen, (2004) but inconsistent with the agency theory's prescription which predicted positive effect on CFP with board composition of majority outside directors. As part of their findings Hooghiemstra and van Manen, (2004) suggested that stakeholders are generally not satisfied with the supervisory role of outside directors.…”
Section: Discussionsupporting
confidence: 71%
“…As part of their findings Hooghiemstra and van Manen, (2004) suggested that stakeholders are generally not satisfied with the supervisory role of outside directors. Similar studies showing negative effect of outside directors on the accounting variables concluded that high proportions of outside directors result in excessive monitoring which stifle innovation and creativity on the part of inside directors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schoorman et al, 2007;Nienaber et al, 2015), but in carrying out their duties, Chairpersons (and the whole Board) are largely dependent on the information provided by the CEO (e.g. Hooghiemstra and Van Manen, 2004;Bailey and Peck, 2013;Koskinen and Lämsä, 2016). This dependence can be assumed to increase vulnerability from the Chair's point of view and can therefore be significant from the perspective of trust.…”
Section: Trust In the Ceo-chair And The Ceo-board Relationshipmentioning
confidence: 99%
“…the ability to monitor objectively. By contrast, firm-specific expertise, in the sense of a deeper business understanding, may increase real independence (Hooghiemstra and van Manen 2004;Wagner 2008). …”
Section: Board Independence and Firm-specific Expertise: The Tradmentioning
confidence: 99%